STRATEGI PENGEMBANGAN USAHA KOPI LUWAK DI KECAMATAN BALIK BUKIT KABUPATEN LAMPUNG BARAT PROVINSI LAMPUNG (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
Luwak Coffee Business Development Strategy in Sub District Bukit West Lampung Regency Lampung Province. The purpose of this research is to analyze internal factors (strengths and weaknesses) and eksetrnal factors (opportunities and threats) and analyze strategy of Luwak coffee business development in Kecamatan Balik Bukit, West Lampung regency, Lampung Province. The method used in this research was a survey method. The Sampling method that used in this research was census method, with a sample of 43 people.The results showed that Internal Factors of Luwak coffee business development in the form of strength (Quality, price, and place), and weaknesses (Tools and technology, financial records, no special network marketing), External Factors in the form of opportunities (The attention of the government, high demand for Luwak coffee), and threats (Competitor, climate change). The strategy of civet coffee business development is to label the Association, improve the quality of the product, and improve the packaging tenology.